Comparing Two Modes of Instruction in English Passive Structures (Processing and Meaning-Based Output Instruction): Membandingkan Dua Mode Instruksi dalam Struktur Pasif Bahasa Inggris (Instruksi Output Berbasis Pemrosesan dan Makna) - Dabiri, Asma (JEES (Journal of English Educators Society), 2018)
This research compared the effects of two types of instruction: Processing Instruction (PI) and Meaning-based Output Instruction (MOI) on the interpretation and production of English passive structures. Ninety EFL intermediate tertiary level female students (PI group= 30, MOI group= 30 and control group = 30) participated in this study. The instruments were a proficiency test, a test to assess English passive structures and two instructional materials (PI and MOI). The data were analyzed by running one-way analysis of variance (ANOVA) and mixed between-within ANOVA. The study indicated the effectiveness of PI and MOI on English passive structures. PI had considerable enhancement on interpretation tasks all the time. It supported the use of PI rather than the use of traditional instructions in which mechanical components were emphasized. Also, the PI and MOI had long term effects on the interpretation and production of English passive sentences. This study supported the use of PI and MOI rather than the use of traditional instruction (TI) in EFL settings. The implication for particularly classroom teaching is that successful grammar instruction has to related to ultimate learning outcomes. Also, creating communicative tasks to offer opportunities for teaching grammar can lead to long-lasting learning effects.